Challenges in setting up a chemical recycling plant: Case of a polyolefins company in the city of Cartagena de Indias - Tordecilla Acevedo, Verónica; Cantillo, Ana Susana; Medellin Rojas, Juan Camilo; Cárdenas Escobar, Alba Zulay; Álvarez Monterrosa, Sergio Andrés (LACCEI, 2025)
Inadequate plastic waste management poses a pressing environmental challenge, driving the need to adopt sustainable business models based on circularity. This research explores the feasibility of establishing the first commercial-scale chemical recycling plant in Colombia, focusing on the transformation of post-consumer polyolefins into new plastics or circular polymers. Through a regulatory, commercial and supply feasibility analysis, together with a financial evaluation using the free cash flow method, we seek to build a business model adapted to the Colombian market. Financial viability, in particular, focuses on determining whether the project's future profits are sufficient to cover costs, operating expenses, and initial investment, ensuring an attractive return for investors. This analysis is based on current global economic indicators and the industrial and technological particularities of the recycling sector in Cartagena and the Caribbean region.